Mixture-of-Mixture Design Using U-Pesdo Components - Saini, Parul; Ashutosh (International Journal of Psychosocial Rehabilitation, 2020)
A Mixture Experiment is defined as an experiment in which the outcome is a function of the proportions of its contents rather than the overall amount. In most of the experimental situations dealing with the mixture, its components are themselves consist of some other sub-components, in such situation it is important to study the individual effect of these sub-components on the response of the final product. The use of components are handled in a way in the experiments that it is important to have the restrictions on of proportions of sub-component in a predetermined way than the proportions themselves. Still there are many situations in which multiple restrictions on major and minor component proportions are imposed. For the development and improvement of product in agricultural and many more allied sectors, mixture experiments are generally used. To construct designs with the help of U-pseudo transformation for Mixture-of-Mixture experiments, upper bound restriction on each of the major and their minor components adopted on U-pseudo designs. For evaluation of the constructed designs, Gefficiencies under various upper restrictions on a number of majors and their minors components are (obtained, which are found) more than 50% which is good enough for the practical point of view.